Effects of photoperiods on the development of Diplonychus rusticus (Fabricius, 1871) (Hemiptera: Belostomatidae): connections to light pollution - Nguyen, Ha Anh; Van Nguyen, Phuc; Duc Tran, Anh; Van Duong, Cuong (Academia Journal of Biology, 2026)
Light pollution caused by artificial light at night has significant impacts on biodiversity, particularly on insects that are strongly attracted to light, by disrupting their physiology and ecological interactions. The aquatic bug, Diplonychus rusticus is an important invertebrate predator in most freshwater habitats of Southeast Asia, particularly in lentic systems such as wetlands and ponds. The species is also known for its high potential in controlling mosquito vectors of transmitted diseases in urban areas, where light pollution has become increasingly prevalent. While the species is not attracted to the light, we aim to examine whether light pollution influences the development, survival and fertility of D. rusticus by exposing them to different photoperiods. Our study revealed that the development time from the first instar to the adult stage was positively correlated with the daily duration of light exposure, whereas the body size (length and width) of all life stages was not affected by photoperiods. In addition, the survival rate and fertility of adult bugs are considerably decreased under prolonged lighting conditions. These results have provided insights into the impacts of light pollution on the aquatic insects that are not attracted to the light showing a necessary strategy for future conservation efforts for insects in urban environments.